Financial position of the automotive industry companies in the Transcarpathian region - Poyda-Nosyk Nina; Pojda-Noszik Nina; Пойда-Носик Ніна; Robert Bacho; Bacsó Róbert; Бачо Роберт (ДВНЗ «УжНУ», 2023)
Abstract. Automotive industry of Transcarpathia has an important leverage effect on state with number of employees, diversity and capacity of the component manufacturers, share in the industry’s income [1]. The region also has shown potential for growth in the automotive industry due to its strategic location, skilled labor force, and proximity to major European markets. Moreover, what is of a paramount importance for nowadays, the region is the safest place for living and running a business in conditions of the martial law in Ukraine. The automotive sector in Transcarpathia began to attract investments and attention, primarily in the form of component manufacturing, assembly, and related services. A large number of companies operating in the Transcarpathian region produce products for the automotive industry.
Keywords: automotive industry; Transcarpathia